(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ANNOTATION: In exploring the magical world of fantasy in children's literature, the essay emphasizes the genre's continuing appeal as well as its significant influence on young readers. Through wacky worlds and fantastic experiences, it examines how fantasy literature ignites the imagination, fosters creativity, and imparts important life lessons. With its fanciful settings, exotic animals, and creative adventures, fantasy plays an engaging and vital role in children's literature, enticing young readers. We go intothe fascinating world of fantasy in children's literature in this piece, emphasizing its relevance, influence, and timeless attraction to young readers.